Understanding Muslim tourist experiences: A Sequential Exploratory Mixed-methods Study of Islamic Values in Destination Marketing - Eko Wediyanto; Taufik Romadon; Ade Titin Sumarni (UNIVED Press, 2026)
This study examines the multidimensional nature of perceived halal tourism benefits among foreign Muslim tourists and identifies market segments based on benefit preferences. Using Exploratory Factor Analysis (EFA), K-means cluster analysis, and Analysis of Variance (ANOVA), the findings reveal that halal tourism benefits encompass religious, social, emotional, and functional dimensions, indicating that Muslim tourists evaluate destinations through a holistic combination of religious values, comfort, safety, service quality, and emotional experiences. Three distinct segments were identified: tourists with high religiosity and gender ethics sensitivity, tourists oriented toward comprehensive Sharia compliance, and pragmatic tourists prioritizing convenience and safety. Significant differences among segments confirm the heterogeneity of Muslim tourist markets. The study further highlights that tourist experiences are influenced by the interaction of religiosity, socio-cultural factors, technology adoption, and sustainability considerations. By integrating a holistic experiential perspective with benefit-based segmentation, this research contributes to halal tourism literature and provides a foundation for developing adaptive, inclusive, and sustainable destination marketing strategies that address diverse Muslim tourist needs.